Notes: (2) A Beaker Burial from Innerwick, East Lothian: With a Report on the Skeletal Remains (Proceedings of the Society of Antiquaries of Scotland, 1939)
A stone cist was discovered during ploughing. It comprised four side slabs with a cover slab and was orientated broadly west-east. The cist contained a Beaker vessel and the fragmented remains of a skeleton aged 3-5 years.